Development of A Tax Aware Clinic Website for MSMEs - Arniati; Anggraini, Ria; Putri, Wika Arsanti; Kurniawan, Dedi; Maulana Putra, Tengku Surya; Maulana Putra, Anjelina; Hasanah, Afriyanti (Politeknik Negeri Madiun, 2026)
MSMEs in Indonesia contribute 61.07% to GDP and absorb 97% of the national workforce. However, their income tax contribution was only 1.1% in 2019. This glaring gap indicates that existing tax information channels, including the Directorate General of Taxes (DGT) portal, fail to effectively reach and serve MSMEs. This study aims to analyze the needs of MSMEs for specialized tax services through a dedicated tax clinic web platform. Research data were obtained from 17 informants through in-depth interviews and focus group discussions (FGDs) that were analyzed using open, axial, and selective coding. A key methodological contribution is the direct link between FGD insights and design features: for example, informants' distrust and discomfort with DGT-managed consultations, feeling